The Relationship between Resiliency and Five Dimensions of Personality in Nurses and Paramedical staff in Lar and Gerash hospitals - Mohammad-Rafi Bazrafshan; Samira Zahmatbar; Hamed Delam; Azizallah Dehghan; Mozhgan Jokar; Esmaeil Kavi (Shiraz University of Medical Sciences, 2019)
Background: Resiliency is considered as a coping method for nurses in dealing with work problems. Because different personality characteristics also cause different responses by nurses in coping with challenges, this study was conducted to investigate the relationship between personality traits and resilience in Nurses and Paramedical staff in Lar and Gerash hospitals. Methods: This is a cross-sectional study. The research sample consisted of 160 nurses and paramedical staff in Lar and Gerash hospitals that were selected by convenience sampling strategy. To measure the variables, NEO Personality Inventory (NEO- FEI) and Connor - Davidson Resiliency Scale (CD-RISC) were used. Data were analyzed using Pearson correlation coefficient in SPSS version 25 software. Results: Statistical analysis showed that extraversion personality traits (r=0.680, P<0.001), openness to experience (r=0.452, P<0.001), agreeableness (r=0.298, P<0.001), and conscientiousness (r=0.635, P<0.001) had a positive and significant correlation with the resiliency variable, and it was only the trait of neuroticism (r=-0.749, P<0.001) that had an inverse and significant correlation with the resiliency variable. Conclusion: In the nursing profession, resiliency is a key element in improving the mental health of nursing staff and helping them to cope better with their stress, challenges and difficulties. Therefore, awareness of the effect of the nurses' personality traits leads to better management, and since resilience is an educable and changeable variable, problems with nurses who lack effective personality traits can be improved by increasing resiliency